Dampak Pengetahuan Dan Sikap Membentuk Keuangan Keperilakuan Serta Kapabilitas Keuangan - Ilham, Muhammad; Jumady, Edy; Yusuf, Marwah (Universitas Patria Artha, 2025)
MSME actors in traditional markets in Makassar City are faced with a lack or limitation of financial knowledge and attitudes towards finance are not optimal so that they have an impact on behavioral finance and financial capability. Thus, the purpose of this study is to examine the role of financial knowledge and attitudes towards finance with behavioral finance and financial capability. The MSME population of the two traditional markets, namely the Pannampu market and the Terong market, totaled 530. The sampling technique uses purposive sampling with the consideration that at least two years of operation and has a turnover that tends to be low and employees from households which are divided into 56 people in the Pannampu market and 44 people in the Terong market so that the total sample is 100 respondents. Data analysis using SmartPLS. The results showed that financial knowledge has a positive and significant effect on behavioral finance. Furthermore, financial attitudes towards behavioral finance have a positive and significant effect. Finally, behavioral finance has a positive and significant effect on financial capability. This study extends the validity of the results of previous studies, as well as providing practical implications that the better the financial knowledge and financial attitudes, the better the behavioral finance and the better the financial capability by traditional market MSME players.